2021
DOI: 10.1080/21655979.2021.1972901
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA CRNDE exacerbates neuropathic pain in chronic constriction injury-induced(CCI) rats through regulating miR-146a-5p/WNT5A pathway

Abstract: Neuropathic pain (NP) originating from a dysfunction in the nervous system is often intractable and chronic. Many studies have implicated long noncoding RNAs (lncRNAs) in the physiological and pathological development of NP. The lncRNA colorectal neoplasia differentially expressed gene (CRNDE) has been shown to mediate NP progression. However, further investigations are needed to gain deeper understanding of the specific mechanisms governing CRNDE in NP etiopathology. In this study, we successfully used chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“… 330 , 331 Some molecular regulators, such as SFRP1, LPAR3, miR-26a-5p and LncCRNDE, jointly control Wnt/β-catenin signaling-mediated neuropathic pain. 331 334 A recent study demonstrated that GPR177 promotes the secretion of Wnt5a from A-fiber DRG neurons, which further enhances rapid currents of TRPV1+ nociceptive DRG neurons. 335 This finding has strongly revealed the functions of intercellular communications via Wnt/β-catenin signaling during neuropathic pain progression.…”
Section: Molecular Mechanisms Of Pain Modulationmentioning
confidence: 99%
“… 330 , 331 Some molecular regulators, such as SFRP1, LPAR3, miR-26a-5p and LncCRNDE, jointly control Wnt/β-catenin signaling-mediated neuropathic pain. 331 334 A recent study demonstrated that GPR177 promotes the secretion of Wnt5a from A-fiber DRG neurons, which further enhances rapid currents of TRPV1+ nociceptive DRG neurons. 335 This finding has strongly revealed the functions of intercellular communications via Wnt/β-catenin signaling during neuropathic pain progression.…”
Section: Molecular Mechanisms Of Pain Modulationmentioning
confidence: 99%
“…The capsaicin receptor (TRPV1) in mature neurons functions in transducing injurious signals and generating pain as a heat‐sensitive ion channel 14 ; hence, lower TRPV1 expression can effectively inhibit NP progression. 15 WNT5a belongs to the Wingless‐type MMTV integration site family, 16 acting on neurons through the β‐catenin‐independent WNT signaling pathway, and has been reported to be involved in NP development. 17 Recent research indicates that the activation of TRPV1 by WNT5a is essential for NP formation, which is regulated by GPR177, 18 which was an intriguing factor in this study since studies on exploring pathways and regulatory mechanisms in this process are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant expression of lncRNAs is associated with human diseases, particularly in the nervous system, and has been postulated as a therapeutic biomarker for neurogenic diseases. For instance, lncRNA MALAT1 [26], FIRRE [35], PVT1 [42], and CENDES [44] were identified to be involved in the pathological process of NP. Five prime to XIST (FTX) is a highly conserved LncRNA, located on chromosome Xq13.2, containing 2300 nucleotides.…”
Section: Introductionmentioning
confidence: 99%